Digital Transformation Strategies and Financial Resilience of SMEs - Rafat Ahmad, Shai; Habibah Halim, Sharah (Inovasi Analisis Data, 2025)
Purpose: his research explores the effect that digital transformation (DT) strategies have on financial resilience in small and medium-sized enterprises (SMEs), through considering combined impacts of DT strategy implementation, technology investment capability, workforce digital skills, and customer digital engagement, moderated by environmental uncertainty.Method: The research uses firm-level survey data collected from emerging market SMEs applying quantitative approach through hierarchical regression to scrutinize direct and moderating relationships.Findings: The findings of the study reveals that all the four components of digital transformation were found to have large, statistically significant and positive effects on financial resilience. Specifically, we found strong effects on workforce digital skills and customer digital engagement to support a role for human capital and relationships with customers in performing under conditions of crisis. Environmental uncertainty strengthens the positive impact of digital strategy and technology investments, confirming the contingency view that turbulent environments enhance the strategic imperative.Novelty: In contrast to existing studies which treat digital transformation as a unidimensional concept, the current research separates it into strategic, technological, human and relational aspects by incorporating environmental uncertainty as a moderator. Theoretically, we contribute to dynamic capability theory by identifying the boundary conditions that shape resilient outcomes.Implications: Results offer theoretical contributions explaining the multidimensional approach of digital transformation and practical indications for SME managers and policy-makers who have to segment digital initiatives based on sectoral context and degrees of environmental turbulence.